KETERAMPILAN BERPIKIR KRITIS SISWA MELALUI PENERAPAN STRATEGI METAKOGNITIF DI KELAS X PI SMA IT AL-ITTIHAD PEKANBARU - Susi Asmiati Asmiati; Azizahwati '; Zuhdi Ma’aruf Ma’aruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to describe the critical thinking skills of students in class X Pi SMA IT Al-Ittihad Pekanbaru through the implementation of Metacognitive Strategies in lesson temperature and heat. The research used pre-experimental with one group pretest-posttest design. The subjects were students of class X Pi totalling 19 female students. The instrument of data collection in this study is the critical thinking skills test. Analysis of the data in this study is a descriptive analysis to see an overview of the critical thinking skills of student by using 3 criterias are: (1) absorption, (2) increase critical thinking skills of students  in 5 indicators of critical thinking skills (analysis, synthesis, recognize and solve problems, conclude, and evaluate), (3) effectiveness of learning. The research showed the critical thinking skills of student in class X Pi SMA IT al-Ittihad Pekanbaru through the implementation of Metacognitive Strategies in lesson temperature and heat are in good category (70,1%), increase critical thinking skills of students in each of the indicators of critical thinking skills in middle category , and the effectiveness of learning through metacognitive strategies to improve students' critical thinking skills in the category quite effective. Key Words : Metacognitive Strategies, Critical Thinking Skills